Developments in EU migration policy - New Pact on Migration and Asylum - Dufek, Matyáš; Antal, Jarolím, 1986-; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis examines the development of European migration and asylum policy in the period 2014-2023, with an emphasis on the measures taken after the 2015 migration crisis and on the issue of return policy. The first part of the thesis traces the historical evolution of the policies in question and the statistical trends in EU Member States, specifically Italy, Greece and Spain, because of their high burden during the crisis. The second part of the thesis focuses on the impact of key measures on the statistical data in question, for example on the numbers of asylum applications or returnees. The aim is to provide a comprehensive overview of the measures taken and to contribute to the understanding of their relevance in European migration and asylum policy.
Vedoucí práce: Jarolím Antal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses